Az összehasonlító irodalomtudomány és a klasszikusok - Hajdu, Péter (Studia Litteraria, 2015)
The fact that the ICLA’s book series, the comparative history of literatures in European languages, took the Renaissance as its point of departure suggests that the timespan of comparative literature does not go back further than that period. David Damrosch’s definition of world literature, however, includes all the classics as texts read outside their original culture. For a comparative approach we do not need to compare the classics to a different (e.g. modern or a non-European ancient) kind of literature: since all the western literary cultures developed some kind of relationship to the classics, they can be discussed as a code of western literature, which may make them a „language” of comparison.